2007
DOI: 10.1016/j.ijadhadh.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Properties of thermoplastic polyurethane adhesives containing nanosilicas with different specific surface area and silanol content

Abstract: Thermoplastic polyurethane (TPU) adhesives containing nanosilicas with different specific surface area and silanol group content were prepared and characterized by FTIR spectroscopy, differential scanning calorimetry (DSC), thermogravimetry (TGA), X-ray diffraction, plate-plate rheology, dynamical-mechanical-thermal analysis (DMTA), transmission electron microscopy (TEM), and strain-stress test. Adhesive strength was obtained from T-peel tests of PVC/polyurethane adhesive joints.Formation of agglomerates of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 11 publications
1
24
0
6
Order By: Relevance
“…10a. This excellent technique to obtain such micrographs was devised by Pearson and Yee [58] in order to help identify mechanisms occurring at crack tips. Fig.…”
Section: The Shear-banding Mechanismmentioning
confidence: 99%
“…10a. This excellent technique to obtain such micrographs was devised by Pearson and Yee [58] in order to help identify mechanisms occurring at crack tips. Fig.…”
Section: The Shear-banding Mechanismmentioning
confidence: 99%
“…Other authors have confirmed this phenomenon in cases where nano-silica and TiO2 was incorporated into multilayer organic coatings [15][16][17][18][19][20][21][22].…”
Section: Matec Web Of Conferencesmentioning
confidence: 74%
“…Recent studies (Nunes et al, 2000;Nunes et al, 2001;Vega-Baudrit et al, 2006;NavarroBañón et al, 2005;Vega-Baudrit et al, 2008;Vega-Baudrit et al, 2009) have demonstrated that the addition of fillers as silica able to form hydrogen-bonds result in less direct interactions between phases, causing a higher degree of phase separation in the polyurethane. On the other hand, the interactions between the silanol groups and the carbonyl groups in the polyurethane are weaker than those between the N-H and ester carbonyl groups, and therefore the silica addition increases the polyester chain mobility in the polyurethane allowing the creation of more ordered phases with respect to the polyurethane without silica.…”
Section: Resultsmentioning
confidence: 99%
“…In recent papers are showed the results of evaluating these samples using thermal, rheological and mechanical analysis, and adhesion tests (Vega-Baudrit et al, 2006;NavarroBañón et al, 2005;Vega-Baudrit et al, 2008;Vega-Baudrit et al, 2009). …”
Section: Introductionmentioning
confidence: 99%